Source identification, spatio-temporal distribution and ecological risk of persistent organic pollutants in sediments from the upper Danube catchment - Kukučka, Petr; Audy, Ondřej; Kohoutek, Jiří; Holt, Eva; Kalábová, Tereza; Holoubek, Ivan; Klánová, Jana (Chemosphere, 2015)
Riverine sediments, collected on a monthly basis during a period of one year, from five sites in a mixed land use region of the Czech Republic were analysed for chlorinated and brominated persistent organic pollutants (POPs). The region is located in the upper catchment of the Danube River. The POPs concentrations were as follows: 11-930 pg g(-1) polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDDs/Fs), 170-980 pg g(-1) dioxin-like polychlorinated biphenyls (dl-PCBs), 34-13,700 pg g(-1) polychlorinated naphthalenes (PCNs), 5.7-29,200 pg g(-1) polybrominated diphenylethers (PBDEs) and 0.21-351 ng g(-1) hexabromocyclododecanes (HBCDs). Concentrations expressed as toxic equivalents (TEQs), for PCDD/F+dl-PCB+PCN (TEQPCDD/F+dl-PCB+PCN) ranged from 0.37 to 19 pg g(-1). The results revealed a clear spatial separation between sites based on concentration and congener profile. There were also some obvious temporal patterns of selected POPs, which were related to river flow (seasonality) and organic carbon (TOC) of the sediment. Potential sources of POPs include local municipalities (flame retardants), some diffuse sources (PCNs and PCDDs/Fs) and potential point sources (PBDEs). Risk assessment based on risk quotients (RQ) revealed limited to medium ecological risk from PBDEs. TEQPCDD/F+dl-PCB+PCN were low relative to other European rivers, hence the risk to aquatic organisms was considered to be low. PCNs contributed significantly to overall TEQ in several cases.
Keywords: geologické sedimenty; Ecology; hodnocení rizik; chemické látky znečišťující vodu; Water Pollutants, Chemical; monitorování životního prostředí; ekologie; Persistent organic pollutants (POPs); Sediment; Rivers; Hydrocarbons, Chlorinated; Hydrocarbons, Brominated; Risk Assessment; Ecological risk assessment; Source identification; chlorované uhlovodíky; Czech Republic; bromované uhlovodíky; řeky; Environmental Monitoring; Česká republika; Geologic Sediments; Spatio-Temporal Analysis; časoprostorová analýza